Standardizing gross descriptions of skin lesions in common bottlenose dolphins (Tursiops truncatus) stranded in Southwest Florida, 2015–2019 - Ruth Y. Ewing; Meghan N. Sutton; Hada M. Herring; Molly R. Schubert; Denise M. Boyd; Jill L. Richardson; David S. Rotstein (Frontiers in Marine Science, 2023)
As the first line of defense, the integumentary system is critical in comprehensively evaluating dolphin morbidity during stranding response. Most published studies on skin lesions in bottlenose dolphins (Tursiops truncatus) lack standardized gross descriptions and methodologies for evaluating lesions. The primary objective of this study was to evaluate the effectiveness of an assessment matrix designed to consistently describe skin lesions based on a set of standardized gross description characteristics. The matrix was implemented by reviewing necropsy reports, histopathology reports, and photographs collected from bottlenose dolphins stranded in Southwest Florida from 2015 through 2019. Of the 32 dolphins that met the inclusion criteria, 19 presented with skin lesions and five reviewers described each of the 46 lesions according to a novel, standardized assessment matrix. The most common descriptor selected, in each of the respective matrix categories, were, by anatomic location, head; distribution, multifocal to coalescing; quantity, moderate (10–30); size, <2 cm; shape, punctate; margin, rounded; color modifier, hyperpigmentation; texture, smooth; and texture modifier, flat. These prevalent descriptors coincided with the frequent occurrence of histologically described hydropic degeneration (n=7, 15.2%) and were confirmed poxviral lesions in 6.52% (n=3). Identifying lesion patterns using standardized descriptors capitalizes on the unique pathogen tissue tropism and the implementation of certain disease mechanisms in the integumentary system. Therefore, it can facilitate differential disease diagnoses and guide ancillary diagnostics testing. The use of standardized descriptors will aid in etiologic identification and monitoring of skin lesions and associated diseases, advancing our understanding of dolphin morbidity and mortality.